Silica nanoparticles as an enhancer in the IL-1β-induced inflammation cycle of A549 cells. (4th March 2019) - Wu, Jing; Han, Yajing; Zou, Xiaoqian; Zhu, Kehui; Wang, Zichen; Ye, Xiaohong; Liu, Yumei; Dong, Shirui; Chen, Xiaojing; Liu, Dandan; Wen, Zihao; Wang, Yao; et al.
Abstract: Objective: The industrial production and combustion of coal can produce silica nanoparticles (nano-SiO2 ). It enters the human body mainly through the respiratory tract and exerts a toxic effect. However, whether nano-SiO2 can increase the IL-1β-induced inflammatory expression in A549 cells has not been tested. Therefore, the synergistic toxicity of nano-SiO2 and IL-1β to A549 was observed in our study. Materials and methods : We exposed A549 cells to nano-SiO2 (0, 100, 500, and 1000 μg/ml) for 12 and 24 h. The effect of nano-SiO2 on the viability of A549 cells was observed by the CCK-8 method. The A549 cells were exposed to nano-SiO2 (1 mg/mL) and cytokine IL-1β (10 ng/mL) for 4 h, and we detected the expression of IL-1β and IL-6 cytokines by real time quantitative polymerase chain (RT-qPCR) and enzyme linked immunosorbent assay (ELISA). The expression of β-Actin, I-κB, phospho-ERK1/2 (P-ERK1/2 ), total-ERK1/2 (T-ERK1/2 ), phospho-JNK (P-JNK), total-JNK (T-JNK), phospho-P38 (P-P38), and total-P38 (T-P38) in A549 cells was detected by the Western Blot method. Results: The nano-SiO2 treatment resulted in a time-dependent decrease in the viability of A549 cells. The synergistic effect of nano-SiO2 and IL-1β was observed on the new production of IL-1β and IL-6 in A549 cells. The Western blot results showed that nano-SiO2 can increase the expression of IL-1β and IL-6 by promoting the phosphorylation of ERK1/2 and elevating the phosphorylation of I-κB by IL-1β. IL-1β and IL-6 were induced by nano-SiO2, and the IL-1β treatment with 20 μM of I-κBα phosphorylation inhibitor (PD98059) and 20 μM of ERK1/2 inhibitor (BAY11-7082) for 1 h was significantly lower than that of the control group in A549 cells. Discussion and conclusion: These results indicated that nano-SiO2 had a toxic effect on A549 cells, and this effect could increase IL-1β on the A549 cell-induced inflammatory response. The results suggested that the release of IL-1β and IL-6 in A549 was enhanced by the synergistic IL-1β-induced phosphorylation of ERK1/2 and I-κB. This process is similar to a snowball, and it is possible that IL-1β is continuously produced and repeatedly superimposed in A549 cells to produce an inflammatory effect; then, a vicious circle occurs, and an inflammatory storm is accelerated.